Cantando e aprendendo com música - Lima, Eliene Xavier de; Silva, Estanisley Gonçalves da; Silva, Leidimar Antonia da; Bento, Miriam Furtado; Schiavinato , Ricardo Leandro (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf